Community acquired acute kidney injury in South Asia: causes and outcome. A Meta-Analysis - Rubina Naqvi; Huma, Anbreen (Journal of the Pakistan Medical Association, 2023)
Objectives: To collect all studies on acute kidney injury, even with their limitations, done in South Asia to draw a picture about the types of acute kidney injury prevalent in the region. Method: The meta-analysis was conducted in June 2022 and comprised search on PubMed, Medline, Cochrane Library and Google Scholar databases for studies on acute kidney injury done in South Asia regardless of time limit, and published in the English language. Combinations of key words used were ‘community acquired acute kidney injury’ or ‘acute renal failure’ with using individual names of ‘different countries’ in South Asia. Data was extracted and analysed. Results: Of the 31(67.4%) studies subjected to detailed analysis, 17(54.83%) had been done in India, 10(32.25%) in Pakistan, 2(6.45%) in Nepal, and 1(3.22%) each in Bangladesh and Sri Lanka. Overall, there were 16,584 patients with acute kidney injury. There were 16(51.61%) studies focussing on community-acquired acute kidney injury, while 15(48.38%) also included hospital-acquired acute kidney injury. Also, 17(54.83%) studies were prospective and 14(45.16%) were retrospective. Pattern of defining and classifying acute kidney injury varied in the studies. Need for renal replacement was not mentioned universally. Complete recovery reported varied 40-80% and mortality 2.2-52% in the studies analysed. Conclusions: The number of acute kidney injury patients was considerable. Despite variations in definitions, study designs and outcomes, the meta-analysis provides useful information about the pattern of presentation and major causes of community-acquired acute kidney injury in South Asia. Key Words: Acute kidney injury, Community-acquired, South Asia, Meta-analysis.